2017
DOI: 10.5130/ajceb.v17i2.5245
|View full text |Cite
|
Sign up to set email alerts
|

Volume Home Building: The Provision of Sustainability Information for New Homebuyers

Abstract: The new residential housing sector is producing approximately 200,000 homes a year that could benefit from methods to increase sustainability and energy efficiency. Currently, there is limited implementation of sustainability measures beyond mandatory minimum requirements in Australia. New homebuyers are often the scapegoats for the poor sustainability adoption due to their perceived lack of interest and willingness to pay. However, their knowledge and engagement in sustainability is likely to be strongly guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…This was found in the spot investigation of the websites and display suites of the developments. As noted earlier, there was a lack of information and disclosure of the certification to potential purchasers of those from the certified estates; further from a dwelling perspective, this experience supports a large study of the Housing Industry of Australia’s Top 100 homebuilders’ websites and the limited amount of sustainability information communicated by Warren-Myers and McRae (2017). The lack of information could suggest a level of moral hazard, resulting in the distrust or lack of awareness demonstrated by consumers in this study.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This was found in the spot investigation of the websites and display suites of the developments. As noted earlier, there was a lack of information and disclosure of the certification to potential purchasers of those from the certified estates; further from a dwelling perspective, this experience supports a large study of the Housing Industry of Australia’s Top 100 homebuilders’ websites and the limited amount of sustainability information communicated by Warren-Myers and McRae (2017). The lack of information could suggest a level of moral hazard, resulting in the distrust or lack of awareness demonstrated by consumers in this study.…”
Section: Discussionsupporting
confidence: 76%
“…Given respondent responses that the ratings have a role to play in their decision making, perceived value and resale implications, it was puzzling to see the lack of knowledge about the ratings they actually had for their dwelling and development. The lack of awareness supports findings by Warren-Myers (2017), who examined whether new home buyers (consumers) were provided with information pertaining to their six star rating for their dwelling (DweTool1). In the interviewed sample of 20 consumers, 25 per cent actually received a stamped plan or certificate indicating their six star rating.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Yet, Warren-Myers et al's [94] study in a sustainably certified estate using a small sample of new home buyers found that resident engagement with the environmentally friendly aspects of home purchase was limited due to a lack of awareness and trust in sustainability certifications, which stemmed from poor communication of information from the developer and builder to new residents. This lack of awareness and trust is not unsurprising, when limited and often misleading information is provided and communicated to consumers by the volume builders about their homes energy efficiency and sustainability [95,96,97]. Romanach et al [98,99] also identified that residents would seek more energy efficient homes.…”
Section: Energy Efficiency Property Values and Valuationmentioning
confidence: 99%
“…This study used audio recorded semi-structured interviews with 18 Volume Builders as key actors within the industrialized home building system from types of firms including speculative builders, order builders and franchise order builders [21]. These 18 participants represent 55% of the top 20 builders, 32% of the top 50, and 18% of the top 100.…”
Section: Methodsmentioning
confidence: 99%